Acute neurotoxicity following vincristine due to Charcot–Marie–Tooth disease in a young child with medulloblastoma. Issue 3 (18th March 2019) - Kissoon, Trisha; Gururangan, Sridharan; Sladky, John
Abstract: Vincristine (VCR), a microtubule inhibitor that arrests the cell cycle by blocking metaphase of mitosis, is unique among the vinca alkaloids for causing polyneuropathy. Patients with increased risk of VCR neurotoxicity include the elderly and those with prior history of neuropathy-prone medical conditions. Identifying such risk factors prior to the development of neurotoxicity should be a goal prior to VCR administration. Clinicians should obtain a thorough medical and family history of neuropathies in any child scheduled to receive neurotoxic medications to avoid exacerbating an underlying disorder. We report a case of a young child with newly diagnosed medulloblastoma who started treatment on a VCR-containing chemotherapy regimen following surgery and craniospinal radiation. She subsequently developed severe peripheral polyneuropathy and new enhancement of the cranial and nerve roots following a relatively low cumulative dose of VCR and was diagnosed with previously unidentified Charcot–Marie–Tooth disease (CMTD) Type 1A. This case highlights that an evaluation of risk factors should be completed prior to initiation of neurotoxic chemotherapies and advocates for testing for inherited neuropathies such as CMTD even in asymptomatic patients when hereditary neuropathy is suspected.